2015
DOI: 10.1186/s12884-015-0501-8
|View full text |Cite
|
Sign up to set email alerts
|

Transforming maternal and newborn health social norms and practices to increase utilization of health services in rural Bangladesh: a qualitative review

Abstract: BackgroundSince 2008, Participatory Action for Rural Development Innovation (PARI) Development Trust, with the support of Enfants du Monde, has been implementing a maternal and newborn health (MNH) program based on the World Health Organization’s (WHO) framework for Working with Individuals, Families and Communities (IFC) to improve MNH in Netrokona district, Bangladesh. This program aims to empower women and families and increase utilization of quality health services, thereby helping women realize their righ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 8 publications
1
20
1
1
Order By: Relevance
“…Women reported a positive view of the new roles of re‐oriented TBAs, who were said to respond holistically to the women's needs through practical, material, and emotional support during pregnancy, delivery, and postpartum. This is consistent with other studies in Africa, Asia, and Latin America that also observed the potential role of TBAs in providing maternal and child health care service, emotional support, and advice during the antenatal, delivery, and post‐partum period (Bergström & Goodburn, ; Kayombo, ; Saravanan, Turrell, Johnson, & Fraser, ; Taleb et al, ). The CBMNH‐N project found that it is possible to change the behaviour and care practices of TBAs with an appropriate strategy.…”
Section: Discussionsupporting
confidence: 91%
“…Women reported a positive view of the new roles of re‐oriented TBAs, who were said to respond holistically to the women's needs through practical, material, and emotional support during pregnancy, delivery, and postpartum. This is consistent with other studies in Africa, Asia, and Latin America that also observed the potential role of TBAs in providing maternal and child health care service, emotional support, and advice during the antenatal, delivery, and post‐partum period (Bergström & Goodburn, ; Kayombo, ; Saravanan, Turrell, Johnson, & Fraser, ; Taleb et al, ). The CBMNH‐N project found that it is possible to change the behaviour and care practices of TBAs with an appropriate strategy.…”
Section: Discussionsupporting
confidence: 91%
“…BPCR messages were easily understood by women respondents in Nepal and Burkina Faso [ 23 , 52 ]. Studies that used visual aids such as cards, posters or booklets were positively received and understood [ 32 , 42 , 43 , 45 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…31,46,47 Although this is a contested topic within the international community, many stakeholders agree that traditional birth attendants can play an important role in maternal and newborn health. Studies exploring local-level perceptions have found generally positive perceptions regarding traditional birth attendants in rural communities.…”
Section: Discussionmentioning
confidence: 99%
“…Studies exploring local-level perceptions have found generally positive perceptions regarding traditional birth attendants in rural communities. 31,46,47 Although this is a contested topic within the international community, many stakeholders agree that traditional birth attendants can play an important role in maternal and newborn health. 48 In addition, WHO recommends that in areas where traditional birth attendants continue to be the primary health care providers around the time of birth, that the health systems should partner with traditional birth attendants to define and agree on alternative roles for them in supporting the health of women and newborns.…”
Section: F I G U R Ementioning
confidence: 99%